Improved forecast skill in the tropics in the new MiKlip decadal climate predictions. Issue 21 (13th November 2013) - Pohlmann, H.; Müller, W. A.; Kulkarni, K.; Kameswarrao, M.; Matei, D.; Vamborg, F. S. E.; Kadow, C.; Illing, S.; Marotzke, J.
<x xml:space="preserve">Abstract</x> [1] We introduce an improved initialization to the decadal predictions performed for the Mittelfristige Klimaprognosen (MiKlip) project based on the Max‐Planck‐Institute Earth System Model and furthermore test the effect of increased ocean and atmosphere model resolutions. The new initialization includes both a more sophisticated oceanic initialization and additionally an atmospheric initialization. We compare the performance of retrospective decadal forecasts over the past 50 years with that of the previous system. The new oceanic initialization considerably improves the performance in terms of surface air temperature over the tropical oceans on the 2–5 years time scale, which also helps to improve the predictive skill of global mean surface air temperature on this time scale. The higher model resolution improves the predictive skill of surface air temperature over the tropical Pacific even further. Through the newly introduced atmospheric initialization, the quasi‐biennial oscillation exhibits predictive skill of up to 4 years when a sufficiently high vertical atmospheric resolution is used.